Portuguese Guidelines on Neuromuscular Blockade Management - 2017 - Esteves, Simão; Roxo, António; Resendes, Hernâni; Pereira, Luciane; Fernandes, Nuno; Borges, Sandra; Pereira, Sandra; Albuquerque, Susana; Caramelo, Susana; Vargas, Susana; et al. (Journal of the Portuguese Society of Anesthesiology, 2018)
The use of neuromuscular blockers is common in patients undergoing general anesthesia to facilitate tracheal intubation and ventilation and provide adequate surgical conditions. Despite commonly used, they are associated with an increased risk of postoperative complications that are widely described in the literature. One of the factors involved in this risk of complications is the persistence of signs and symptoms of residual neuromuscular blockade in the immediate postoperative period. The literature showed that residual neuromuscular blockade is a common occurrence increasing the likelihood of complications. In Portugal, in a study published in 2013, it was found an incidence of 26% of residual neuromuscular blockade. Aware of this reality the board of Portuguese Society of Anesthesiology decided to name a working group with the mission of elaborating guidelines on the management of neuromuscular blockage in the perioperative period. In the light of this decision, this working group began by drawing up a survey directed to the Anesthesiologists working in Portugal, on matters related to the handling of neuromuscular blockade, to obtain an initial “photography” on these issues. The goal of this group is to draw up a document setting out guidelines for the clinical use of neuromuscular blockers, the monitoring of their effects and appropriate reversion.